Effect of Explosive Reactive Armour Cover Plate on Interaction of ERA and Explosively Formed Projectile. (11th July 2019) - Rasheed, Muhammad F.; Wu, Cheng; Raza, Ali
Abstract : Explosive reactive armour (ERA) is used to protect the armoured vehicles against chemical energy warheads and long-rod penetrators. ERA generally consists of an ERA sandwich and an outer steel cover to protect it from unintended initiation. Explosively formed projectiles (EFPs) are used as antiarmour warheads, and their use in top attack antiarmour weapons is increasing. Interaction of EFP with the ERA sandwich alone has been studied in the past. This paper studies the effect of the cover plate and its thickness on the interaction of the EFP and the ERA sandwich. Numerical simulations and experiments have been used to study the interaction. It has been found that the penetration in the target is reduced as the thickness of the cover plate increases. Moreover, the decrease in penetration is directly proportional to the thickness of the cover plate. Also it has been found that the residual EFP after penetrating the cover plate has sufficient energy to initiate the ERA sandwich. The results of the numerical simulation and the experiments are in close agreement.